From Southern theory to decolonizing sociolinguistics voices, questions and alternatives - Deumert, Ana; Makoni, Sinfree (Studies in knowledge production and participation, 2023)
"This book seeks to imagine a decolonized sociolinguistics. All the chapters are firmly grounded in southern approaches to knowledge production, and invite us to begin to decolonize ourselves and to rethink normative assumptions about everything from academic writing to research methods and language teaching"--